Identificação dos fatores que influenciam na escolha da rota pelos ciclistas: estudo de caso da cidade de São Carlos - Segadilha, Ana Beatriz Pereira (Universidade Federal de São Carlos, 2014)
This study reports on the information obtained by analyzing actual urban bicyclecommuter routes in São Carlos, using Global Positioning Systems (GPSs) for collecting the data and a Geographic Information System (GIS) for analyzing the data. The characteristics of the routes used by cyclists were compared with the characteristics of the shortest-path routes. The extra distance travelled was computed by the difference between these two lengths, and a multiple linear regression was created for explain the reason for this extra distance. The results showed that 70% of the trips were, at most, 15% longer than the shortest path, the average extra distance was 220 meters and the factors that have an influence was the street hierarchy and pavement quality.
Keywords: Planejamento urbano; Acessibilidade e mobilidade; Bicicleta; Sistemas de informação geográfica; Sistema de posicionamento global; Sig; Gps; Análise de rotas; Escolha de rotas; Bicycle; Route analyses; Route choice; ENGENHARIAS